Quantitative design methods of corrosion protection the reinforced concrete structures at the stages of the life cycle (2019)
Concrete and reinforced concrete are the main structural materials in modern construction. The area and volumes of application of these materials continues to expand. In recent years, in the practice of construction, there is a tendency to the use of structures that combine load-bearing and enclosing functions, as well as the functions of technological equipment. At the same time, their working conditions are becoming more complicated and harsh. In addition to the usual force effects (loads), structures are exposed to all kinds of environmental influences (actions) in the form of substances, energy, or a combination thereof. According to current design standards in reinforced concrete structures designed to work in aggressive environments corrosion of materials is not allowed. However, there is a large amount of structures that have received corrosion damage at the operation stage. The standards do not contain any guidelines for designing a parameters of the primary protection and repair system for reinforced concrete structures and their elements (durability forecast, repair period, determination of structural and technological parameters of the primary protection or repair systems). Thus, there are tasks of designing the protection of reinforced concrete structures both at the design stage and at the operation stage. At the design stage, it is necessary to determine the structural and technological parameters of the primary protection that ensure the service life of structures or the period between repairs. At the stage of operation, it is necessary to determine the parameters of repair systems which provide the residual service life until the next repair or liquidation of reinforced concrete structures. Our research shows the economic feasibility of designing reinforced concrete structures interacting with aggressive environment, taking into account the kinetics of concrete corrosion. The optimal design methods can be used to obtain the most economical solutions. We have developed quantitative methodology for the design of primary protection of reinforced concrete structures.